The measurement of effective internal shariah audit function in Islamic financial institutions - Ab Ghani, Nur Laili; Mohd Ariffin, Noraini; Abdul Rahman, Abdul Rahim (Kulliyyah of Economics, International Islamic University Malaysia, 2019)
Assurance of Sharīʿah compliance through the Sharīʿah audit function is crucial for enhancing the integrity of Islamic Financial Institutions (IFIs). Effective Sharīʿah audit function during periodical assessment will ensure effective internal control system for Sharīʿah compliance in IFIs. This paper examines the measurement of effective internal Sharīʿah audit function in IFIs. It critically reviews the emerging literature on the importance of eight components for measuring effective internal Sharīʿah audit function. The components are Sharīʿah audit objective, Sharīʿah audit scope, Sharīʿah audit and governance, Sharīʿah audit charter, competency of internal Sharīʿah auditors, Sharīʿah audit process, reporting requirements and independence. These components are important for achieving effective internal control over Sharīʿah compliance. The study also performs a structured interview with Islamic financial experts to validate the measurement before it is further examined in future empirical studies. The main argument of this paper is that highly effective internal Sharīʿah audit function leads to inclusive opinion on reasonable assurance of Sharīʿah compliance. Assurance of Sharīʿah compliance should enhance stakeholder confidence and satisfy the growing demand for IFIs accountability and sustainability.